2013
DOI: 10.26719/2013.19.9.812
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of rubella among pregnant women in Khartoum state, Sudan

Abstract: Rubella vaccine is not included in the Sudanese national immunization programme, and data on the prevalence of rubella among women of childbearing age are inadequate. The objective of this cross-sectional study was to determine the seroprevalence of rubella among pregnant women in Khartoum state, Sudan. A total of 500 pregnant women who visited 7 antenatal clinics from November 2008 to March 2009 were examined for the presence of rubella IgG antibodies using ELISA. Rubella IgG antibodies were detected in 95.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 6 publications
6
14
1
Order By: Relevance
“…(Barreto et al, 2006). In mounting body of study conducted among Sudanese women, Rubella virus was detected in 65.3% (Hamdan et al, 2011) and 95.1% (Adam et al, 2013). In growing number of studies conducted in Turkey, rubella seropositivity among pregnant women was reported to be between 93.8 and 100% (Aksakal et al, 2007;Pehlivan et al, 2007;Seker et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(Barreto et al, 2006). In mounting body of study conducted among Sudanese women, Rubella virus was detected in 65.3% (Hamdan et al, 2011) and 95.1% (Adam et al, 2013). In growing number of studies conducted in Turkey, rubella seropositivity among pregnant women was reported to be between 93.8 and 100% (Aksakal et al, 2007;Pehlivan et al, 2007;Seker et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All countries surveyed, having a developed or developing status, had national vaccination programmes. However, of the countries in the least developed status, two of the 13 countries (Guinea-Bissau and Bangladesh) [10,25,70,77,89] reporting measles serosurveys and six of the eight countries (Bangladesh, Burkina Faso, Nepal, Nigeria, Sudan and Tanzania) [25,54,56,81,85,97,98] reporting rubella serosurveys reported having no nationally coordinated vaccination programme at the time of the study. Forty-three percent of published measles serosurveys were conducted in developed countries, reflecting the need to identify susceptible populations and immunization gaps as these countries move towards achieving the measles elimination goal.…”
Section: Countries In Which Studies Were Conductedmentioning
confidence: 97%
“…Rubella infection is considered relatively benign, and in the absence of pregnancy, the infection is usually mild and self-limiting (CDC, 2001). However, during pregnancy, it has a devastating effect on the developing fetus (Adam et al, 2013;Cradock-Watson et al, 1981) and this represents a major health concern worldwide (Mirambo et al, 2015). Currently, there is no specific treatment for the virus (Olajide et al, 2015).…”
Section: Introductionmentioning
confidence: 99%